(untitled) (Global Journal of Human-Social Science, 2020)
The study on the locus of control (LOC) of retired public servants in Akwa Ibom State on their post-retirement adjustment used 299 respondents. A 34 item Retired Public Servants Opinion Questionnaire (REPSOQ) was used to elicit information on the retirees’ feelings on LOC and their postretirement satisfaction of health, social, emotional, and economic indices. A null hypothesis of no significant influence of LOC on post-retirement adjustment of public servants was used in our test using an independent t-test at 0.05 level of significance and df of 297. The result showed no significant difference between retirees with internal and external LOC. Retirees with external LOC had significantly higher health adjustment than those with internal LOC. Retirement adjustment remains a problem for retirees in Nigeria as they struggle for their legitimate entitlement. Post-retirement counselling is recommended to be integrated into retirement package, and retirement engagement like seminars on career termination, healthcare and financial management programs should be designed for the retired persons before and after retirement at scheduled periods to keep them abreast of events.